OVERCONFIDENCE AND ILLUSION OF CONTROL IMPACT ON INVESTORS'S DECISION MAKING - Mujahid Bilal; Erbina Meliana Purba; Hashim Hussain; Amna Batool; Dewi Kartikaningsih; Robby Simanjuntak (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The primary purpose of this research is to examine the impact of two biases, i.e., overconfidence and illusion of control, on the investor's decisions on the Karachi Stock Exchange (KSE) 100 Index by using ammo. Data were analyzed using SEM from the sample consisting of 400 respondents. This research shows that past information leads investors to be overconfident. Males are more overconfident than females. Investors do not focus much on fundamental or technical analysis in their decisions. So, that is why results show that overconfidence significantly impacts investor decision-making process in KSE 100 Index. Similarly, the illusion of control is also a bias recognized by behavior finance, which openly or not directly impacts trading behavior in the stock market. The bias of illusion of control significantly and negatively impacts the investor decision-making process in KSE 100 Index.